Development and implementation of promising technologies in JSC EDB Fakel - E. A. Bogdanova; I. Y. Ponomarev; A. V. Nasedkin (Космические аппараты и технологии)
The enterprise is mastering a number of technologies for obtaining functional materials for monopropellant thruster and Hall-effect thruster. The article describes advances in the development of a catalyst for the decomposition of hydrazine with high physicochemical characteristics. The activity of the catalyst assessed by chemisorption H2. The maximum values obtained in the range of 700–750 °C and amounted to more than 1000 µmol/g. The mechanical strength of the granules determined as a result of dynamic and static tests: 0.5 % and 16 MPa. The specific surface area according to the BET method was about 110 m2/g. As part of the work on a new low-temperature emissive material, samples of electrides mayenite obtained by solidphase synthesis. The results of laboratory tests indicate that the emission current has reached 1 mA, but at the moment long-term stable operation of the emitter has not been achieved. As part of the work on testing the application of a hafnium nitride barrier coating, prototypes of coatings on standard parts of the cathode assembly obtained and investigated. The coating is characterized by uniform thickness and color, and high adhesion to substrate. In continuation of the work, it is planned to conduct fire tests as part of the engine.